1969
DOI: 10.1161/01.res.25.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Saline Loading on the Renin, Erythropoietin, and Blood Pressure Responses to Canine Renal Allotransplantation

Abstract: Serial determinations of plasma erythropoietin and renin activities and mean arterial blood pressure were done in five dogs before and after renal allotransplantation. Throughout the experiment, the animals were given 154 mEq of NaCl per day, starting 1 week before transplantation. No immunosuppressive therapy was given. Onset of immunological rejection was determined by daily measurement of endogenous creatinine clearance. Arterial pressure and plasma erythropoietin concentration increased markedly at the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1970
1970
1988
1988

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The erythropoietin levels in this case did not show any correlation with t h e plasma renin levels, confirming the opinion of other workers who have suggested that they are stimulated independently (Abbrecht et al, 1969).…”
Section: Discussionsupporting
confidence: 88%
“…The erythropoietin levels in this case did not show any correlation with t h e plasma renin levels, confirming the opinion of other workers who have suggested that they are stimulated independently (Abbrecht et al, 1969).…”
Section: Discussionsupporting
confidence: 88%
“…Thus, ESF elevations as observed in the present series of experiments (Tables I and 11) reflect essentially renal foci or stimuli. In contrast, as in man (Capelli et al, 1968), extrarenal renin sources are known to exist in the dog. Variations or the lack of them as noted in the currently reported experiments may in part also be influenced by this feature.…”
Section: Discussionmentioning
confidence: 90%